Ferroelectric domain evolution in gold nanoparticle-modified perovskite barium titanate ceramics by piezoresponse force microscopy - J. Nonkumwong (2018)
© 2018 Taylor & Francis Group, LLC. This work addresses the domain evolution processes in polycrystalline barium titanate (BaTiO3, BT)-based ceramics containing various amounts of gold nanoparticles (AuNPs) as an additive by using piezoresponse force microscopy (PFM). The obtained PFM images of the AuNPs-modified BT ceramics revealing the change of one spontaneously polarized state to another under various applied direct current (DC) voltage are discussed in terms of their domain topology, PFM phase shift and PFM amplitude. In general, complex microstructures containing almost round-shaped and micron-sized grains, and grain boundary regions are clearly seen in the topographic images of all samples. The obtained results point towards possibility of control the polarization switching of the AuNPs-modified BT ceramics with fined-grains sizes, by a selection of the proper applied DC voltage (VDC). The PFM investigation confirmed good dipole orientation within the AuNPs-modified BT ceramics containing submicron grain size at the elevated external fields and proved the lack of convenient domain switching of the unmodified BT case resulting from their larger grain size.